2013
DOI: 10.3819/ccbr.2013.80003
|View full text |Cite
|
Sign up to set email alerts
|

Neurobiological foundations of an attribute model of memory

Abstract: Memory is a complex phenomenon due to a large number of potential interactions that are associated with the organization of memory at the psychological and neural system level. In this review article a tripartite, multiple attribute, multiple process memory model with different forms of memory and its neurobiological underpinnings is represented in terms of the nature, structure or content of information representation as a set of different attributes including language, time, place, response, reward value (af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 202 publications
(218 reference statements)
1
4
0
Order By: Relevance
“…They found that the CA1 lesions disrupted learning when events to be associated were separated in time but not presented together, and this is not the case for CA3 (for review, see Kesner 2013, Kesner et al 2005. This is consistent with findings from Huerta et al (2000) who subjected hippocampal CA1 pyramidal cell-specific-NMDA receptor knockout mice (Tsien et al 1996) to trace fear conditioning.…”
Section: The Hippocampal Ca1 Area Supports Temporal Associative Learningsupporting
confidence: 54%
“…They found that the CA1 lesions disrupted learning when events to be associated were separated in time but not presented together, and this is not the case for CA3 (for review, see Kesner 2013, Kesner et al 2005. This is consistent with findings from Huerta et al (2000) who subjected hippocampal CA1 pyramidal cell-specific-NMDA receptor knockout mice (Tsien et al 1996) to trace fear conditioning.…”
Section: The Hippocampal Ca1 Area Supports Temporal Associative Learningsupporting
confidence: 54%
“…Following Schacter and Tulving (1994) definition of memory systems based on the kind of information represented, this model postulates the presence of event-based, knowledge-based, and rule-based memory systems, each constituted of a number of attributes (forms of memory): time, place, response, reward value, sensory perception, to which language is added in humans (Kesner, 2013; Kesner & Conner, 1972; Kesner, 1980; Kesner & DiMattia, 1987; Kesner, 2009). The event-based system deals with new and incoming information, which is egocentric oriented towards personally-experienced events (similar to episodic memory in MTL model) ; the knowledge-based system encompasses permanent representations stored in long-term memory, which relate to general knowledge about the world (similar to semantic memory in the MTL model); and the rule-based system integrates information from the event-based and knowledge-based systems through rules and strategies with the goal of subsequent action.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is not involved in coding information based on expected nonvarying information in the form of maps, rules, strategies and procedures (knowledgebased memory; 23 ). It is assumed by each of these models that in new learning situa tions the hippocampus is involved in consolidating new information, and in familiar situations, requiring attention or memory for trial unique stimuli, and is involved in temporarily maintaining information across time.…”
Section: All Authors Contributed To the Conception Design And Prepamentioning
confidence: 99%
“…To remedy this situation, Kesner [19][20][21] proposed a tripartite attribute based theoretical model of memory which is organised into eventbased (databased), know ledgebased (expectationbased) and rulebased memory systems. Each system is composed of the same set of attributes or domains of memory, characterised by a set of process ori ented operating characteristics and mapped onto interconnected neural circuits.…”
Section: The Attribute Modelmentioning
confidence: 99%
See 1 more Smart Citation